VD_FINDINFO Jug / 2011 / 157 vom 21. März 2011 - VD Tribunal cantonal (2011)
COAUTEURDROIT PÉNAL, COMPLICITÉ, BRIGANDAGE, FIXATION DE LA PEINE | 140 CP, 144 al. 1 CP, 25 CP, 34 CP, 47 CP, 135 al. 2 CPP (CH), 398 al. 3 let. a CPP (CH), 398 al. 3 let. b CPP (CH)